Improvement on EVESPA for Beamforming and Direction of Arrival Estimation. (13th March 2011) - Racine Racine, Emmanuel Emmanuel; Grenier Grenier, Dominic Dominic
Abstract : This paper presents an alternative estimation procedure of the generalized steering matrix of the sources in EVESPA, suitable for both beamforming and direction of arrival estimation. It is shown how the estimation of such a matrix can be restricted to that of its corresponding coefficient matrix in the signal subspace, providing both performance enhancement and computational complexity reduction. Performance comparison through numerical simulations is presented to confirm the effectiveness of the proposed procedure.